Anticancer metallopharmaceutical agents based on mixed‐ligand palladium(II) complexes with dithiocarbamates and tertiary organophosphine ligands. (17th June 2013) - Khan, Hizbullah; Badshah, Amin; Said, Muhammad; Murtaza, Ghulam; Ahmad, Jamil; Jean‐Claude, Bertrand J.; Todorova, Margarita; Butler, Ian S.
Abstract : Mixed‐ligand palladium(II) complexes of the type [(DT)Pd(PR3 )Cl], where DT = diethyldithiocarbamate (1), dibutyldithiocarbamate (2, 3), dipropyldithiocarbamate (4, 5), bis(2‐methoxyethyl)dithiocarbamate; PR3  = benzyldiphenylphosphine (1, 4), diphenyl‐ o ‐tolylphosphine (2), diphenyl‐ t ‐butylphosphine (3), P‐chlorodiphenylphosphine (5) and triphenylphosphine (6), have been synthesized and characterized by elemental analyses and FT‐IR, Raman and multinuclear NMR spectroscopy. The structures of compounds 1 and 2 were determined by single‐crystal X‐ray diffraction (XRD) measurements and these analyses showed that the complexes have pseudo square‐planar geometry around the Pd(II) and that the dithiocarbamate ligand is bound in a bidentate fashion, while the remaining two positions are occupied by a tertiary organophosphine and a chloride ligand. The anticancer studies showed that the Pd(II) complexes are highly active against cisplatin‐resistant DU145 human prostate carcinoma (HTB‐81) cells with the highest activity shown by compound 6 (IC50  = 2.12 µm ). The redox behavior and ds‐DNA‐denaturing ability of the complexes were studied by cyclic voltammetry and two reduction and one oxidation waves were observed. The decrease in the reduction peak currents illustrated the consumption of the mixed‐ligand drug by the DNA molecule. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We describe the synthesis, characterization and biological activities of six mixed ligand Pd(II) complexes with dithiocarbamates and organophosphine ligands. The complexes, Pd(diethyldithiocarbamate)(PPh2 ‐benzyl)Cl (complex1 ) and Pd(bis(2‐methoxyethyl)‐dithiocarbamate)(PPh3 )Cl (complex6 ) have revealed promising anticancer activity against cisplatin‐resistant DU145 human prostate carcinoma (HTB‐81) cells.